The Effect of Emotion Regulation Training to Reduce Stress among Unemployed Individual at Salafusolikhin Pekalongan Central Java - Muttaqin, Emir (EMPATHY Jurnal Fakultas Psikologi, 2012)
Abstract This study aimed to determine the effect of emotion regulation training to reduce stress on the unemployment rate. Subjects were unemployed person who live in the boarding school Salafusolikhin Pekalongan Central Java. The research methods in this study used an experimental method. Methods of data collection used the stress scale. The method of data analysis in this study used t-test analysis techniques. The results showed a significance level of p = 0.000 (p <0.01) on the difference in the stress level of subjects. It shows that there is a significant difference in stress between the experimental group were given training in emotion regulation with the control group were not given the treatment. The categorization of stress of the subjects showed in the medium category. The research concluded that there is a difference in stress levels after the subjects are given emotional regulation training. This means that the hypothesis is accepted and shows that emotion regulation training can reduce stress on the unemployed.   Keywords: emotional stress, unemployed, and emotion regulation training.